Рідкісні види рослин у степовому культурфітоценозі: систематичний склад, созологічна характеристика, історичні аспекти інтродукції та сучасний стан - Gritsenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The list of the rare species of plants of steppe culturphytocoenose in the botanical-geographic plot site "Steppes of Ukraine" in M.M. Gryshko National Botanical Gardens of the NAS of Ukraine was established. Rare species are analyzed by the systematic composition, sozological statuses, the historical aspects of the introduction, the contem porary state. The efficiency of retention and pro tection of these rare species of the plants ex situ is substantiated.